The Influence of CSR Communication on Legitimacy, Trust and Reputation of BPJS Ketenagakerjaan - Radisatra, Brian; Ganiem, Leila Mona (Marqcha Institute, 2025)
This study analyzes the impact of CSR communication on corporate legitimacy, trust, and reputation at BPJS Ketenagakerjaan using a quantitative approach with SEM-PLS. A total of 315 participants were selected through purposive sampling. The findings show that CSR communication significantly influences corporate legitimacy (β = 0.948, p < 0.001), trust (β = 0.990, p < 0.001), and reputation (β = 0.678, p < 0.001). Corporate legitimacy mediates the link between CSR communication and reputation (β = 0.423, p < 0.001), while corporate trust does not (β = 0.129, p = 0.078). Theoretically, this study supports legitimacy and social exchange theories, highlighting that transparent CSR communication enhances trust and reputation in public institutions. It also underscores the role of corporate legitimacy in strengthening reputation. From a managerial perspective, transparency in CSR communication, value-driven messaging, and proactive CSR programs are crucial. BPJS Ketenagakerjaan should integrate CSR into its communication strategy to improve public perception and credibility